Memórias da Administração da Enfermagem de um Hospital de ensino em Fortaleza-Ce: (RE) construção a partir da história oral - Resende, Eliana de Goes (2012)
The objective of this study is to understand the historical trajectory of the administration of nursing at the University Hospital Walter Cantídio the period 1959 to 2011, from the narrative of ten nurses who took the highest position in nursing administration at the University Hospital since 1959, the year of his foundation until the year 2011. It is a social-historical research, a qualitative approach, which is the predominant method of oral history. Oral history brings the prospect of receiving revelations, secrets, details, etc.., So that some subjective aspect that may seem today will be clarified as well as being a modern resort that makes possible the recovery of memory and (re ) construction of history from the very words of those who experienced and participated in a given period, by their references and also his imagination. The data was through a survey of nursing management of documents HUWC who were in the central file and in the office of the office of the Coordination of nursing, such as reports, photographs, internal communications, planning for services, among others and through interviews with the nurses identified. The enterview were recorded, transcribed in full and returned to the interviewees make the verification of the reliability of the transcripts at that time there were some adjustments, fruits of new memories of the interviewees. Were also gathered documents and photos kindly provided bythe nurses interviewed. The interviews were analyzed through the use of interpretive hermeneutics – dialectic. The study was approved by the Ethics Committee in Research of Hospital University Walter Cantídio (CEP/HUWC). The history-social this result production was organized according to chronological history experienced by the protagonists and announces some issues that accompany the story of the administration of nursing HUWC, as the struggle for professional development, the relationship of power, desire and need for knowledge and scientific and technological advances, the relationship multidisciplinary, humanization of the team finally has a cycle that does not denote a linear process sequenced. In fact demonstrates a non-linear process that occurs by advances and retreats in historic times deferent, with different dynamics given the deferential historical and social conditions inherent to each person interviewed. So, like any story, that it does not end with this dissertation. It just opens the way to be traveled by others so that all is not lost and, as Le Goff recalled, the story is the daughter of memory, deservedly, have to be careful.